PENGARUH STRATEGI GUIDED WRITING UNTUK MENINGKATKAN KETERAMPILAN MENULIS SISWA KELAS V SD NEGERI 187 PEKANBARU - Citra Cintiya; Zufriady Zufriady (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
This research is motivated by the low writing skills of fifth-grade students of SD Negeri 187 Pekanbaru. The low writing skills are caused by the difficulty of writing descriptions that are in accordance with the Indonesian writing rules. In addition, they are less creative in developing ideas that are in their minds. The purpose of this study was to determine the differences and the effect of writing essay skills between students who learned using guided writing strategies with students who study conventionally. This research is a quasi-experimental research subject with class V students of SD Negeri 187 Pekanbaru. The results showed that there was an effect of guided writing strategy to improve the essay writing skills of the fifth-grade students of SD Negeri 187 Pekanbaru. It can be seen from the increase in description essay writing skills from the average initial test 68.82 to 76.82 in the final test with an average increase of 0.27 low categories. While the control class had an initial increase in the initial test of 69.26 to 70.51 in the final test with an average increase of 0.12 in the low category. The guided writing strategy has an influence with a very strong level of relationship with a coefficient of 0.838 and a coefficient of determination of 70.22%, in other words, a guided writing strategy can improve students' essay writing skills.